2010
DOI: 10.1111/j.1468-3083.2010.03954.x
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of preoperative hybrid SPECT/CT in detection of sentinel lymph nodes in cutaneous head and neck malignancies

Abstract: SPECT/CT is an innovative imaging technique, reliably and readily providing additional anatomical/functional information to detect and to excise SLN in the head and neck region. Therefore, SLNE with SPECT/CT-technique is an attractive option to improve the detection of SLN in cutaneous head and neck malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 36 publications
(45 reference statements)
1
19
0
8
Order By: Relevance
“…With the SPECT/CT-guided SLNE, we removed more SLNs (2.40 SLNs per patient) than in the standard cohort (1.87 SLNs per patient, PϽ.001), which is consistent with previous studies. 20,26,29 This finding can be explained by excised nodes near the injection site, which are more clearly visualized with SPECT/CT and the detection of SLN with a weak tracer signal. The additional SLNs excised in the SPECT/CT cohort resulted in no increase in morbidity.…”
Section: Commentmentioning
confidence: 89%
See 2 more Smart Citations
“…With the SPECT/CT-guided SLNE, we removed more SLNs (2.40 SLNs per patient) than in the standard cohort (1.87 SLNs per patient, PϽ.001), which is consistent with previous studies. 20,26,29 This finding can be explained by excised nodes near the injection site, which are more clearly visualized with SPECT/CT and the detection of SLN with a weak tracer signal. The additional SLNs excised in the SPECT/CT cohort resulted in no increase in morbidity.…”
Section: Commentmentioning
confidence: 89%
“…Our study confirms the improved identification of SLNs in overweight patients with melanoma (Table 1) 17 as well as those with tumors in the head and neck area. 20,26 In the head and neck area, we used smaller incisions as well as alternative entry points due to the exact anatomical localization of the SLN. For example, if SPECT/CT demonstrates that the SLN is not under the sternocleidomastoid muscle but on the dorsal margin of the muscle, the surgeon is able to choose a different surgical entry point (FIGURE 2).…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…The superior anatomical information provided by SPECT/CT may lead to modification of the surgical approach as shown in 11 out of 38 patients (29 %) with head and neck melanoma; in six of these 38 patients, SPECT/CT detected additional SNs (16 %) [22]. In another study, SPECT/CT modified the surgical approach (more superficial incision or incision at other site) in 9 out of 34 (27 %) patients with head and neck malignancies [23]. The surgical adjustment rate due to additional information from SPECT/CT increases when SNs are located in the periparotid areas; in eight out of 14 patients (57 %) with melanoma and drainage to the parotid region on planar lymphoscintigraphy, SPECT/CT was able to distinguish SNs in level II of the neck from those located in or around the parotid [24].…”
Section: Head and Neck Malignanciesmentioning
confidence: 96%
“…Overall, in 8-43 % of melanoma patients, 3D imaging identified SLNs that were missed on planar imaging [24]. Preoperative SPECT/CT imaging may also have an impact on surgical management in the complex HN area, by improving the esthetic results, reducing the operating time, and influencing patient outcome [25,26]. Stoffels et al found a higher rate of 4-year disease-free survival in melanoma patients when using SPECT/CT in addition to planar imaging [27].…”
Section: Preoperative 3d Imaging (Spect/ct)mentioning
confidence: 99%